Effect of cut-off frequency of butterworth filter on detectability and contrast of hot and cold regions in Tc-99m SPECT - Sayed, Inayatullah Shah; Mohamed Nasrudin, Nor Syahirah (Scientific Research Publishing, 2016)
In SPECT, noise is one of the major limitations that degrade image quality. To suppress the noisy signals in an image, digital filters are most commonly applied. However, in SPECT image recon-struction, selection of an appropriate filter and its functions has always remained a difficult task. In this work an attempt was made to investigate the effects of varying cut-off frequencies and in keeping the order of Butterworth filter constant on detectability and contrast of hot and cold re-gions images. A new insert simulating hot and cold regions which provides similar views in a re-constructed image was placed in the phantom’s cylindrical source tank and imaged. Tc-99m ra-dionuclide was distributed uniformly in the phantom. SPECT data were collected in a 20% energy window centered at 140 keV by a Philips ADAC Forte dual head gamma camera mounted with a LEHR collimator. Images were generated by using the filtered backprojection technique. A But-terworth filter of order 5 with cut-off frequencies 0.35 and 0.45 cycles.cm-1 was applied. Images were examined in terms of hot and cold regions, detectability and contrast. Results show that the hot and cold regions’ detectability and contrast vary with the change of cut-off frequency. With a 0.45 cycles.cm-1 cut-off frequency a significant enhancement in contrast of cold regions was achieved as compared to a 0.35 cycles.cm-1 cut-off frequency. Furthermore, the detectability of hot and cold regions improved with the use of a 0.45 cycles.cm-1 cut-off frequency. In conclusion, image quality of hot and cold regions affected in a different way with a change of cut-off frequency. Thus, care should be taken in selecting the filter cut-off frequency prior to reconstruction of images; particularly, when both types of regions are expected in the reconstructed image.